Conceptual Study about Farmer Producer Company (FPC): An Organisational Perspectives - Dilip Rasiklal Vahoniya; Nikita Dilip Vahoniya; Jerul R. Halpati (Current Topics on Business, Economics and Finance Vol. 7, 2023)
This article concentrates on the concept of a Farmer producer company (FPC) or Producer Company (PC) like the basic objectives, activities, benefits, registration processes, the formation, memorandum, and article of association of the FPC. Farmers’ producer companies can be seen as hybrids between private companies and cooperative societies. The producer-company concept is aimed to combine the efficiency of a company with the `spirit’ of traditional cooperatives. Producer companies aim to integrate smallholders into modern supply networks öminimizing transaction and coordination costs while benefiting from economies of scale. A producer company is a legal entity created for farmers with the purpose of raising their status, income, and profitability. The traits and legal framework of a cooperative society and a private limited company are owned by a producer company. Through the article researcher try to highlight the objectives of the other legal form of Producer Organisation (PO) like the Cooperative Society Act and Multistate Cooperative Society Act and highlight the objectives of non – a profit legal form of Producer Organisation (PO) like Society registered according to the Society Registration Act, Public Trust registered according to the Indian Trust Act and company registered according to the Section 25 of Indian Companies Act, 1956, as modified as Section 8 in The Companies Act, 2013. The FPC (Farmer Producer Company) will also generate entrepreneurship behavior and interests in the farmers and Indian youth for the primary activities of agriculture and allied sectors due to different activities and easy formation & registration steps of FPC.